Definitive chemoradiotherapy versus esophagectomy in patients with clinical T1bN0M0 esophageal squamous cell carcinoma: A retrospective study. (September 2021) - Jo, Yoon Young; Yu, Jesang; Song, Kye Jin; Jang, Jeong Yun; Yoo, Ye Jin; Kim, Sung-Bae; Park, Sook Ryun; Kim, Yong-Hee; Kim, Hyeong Ryul; Kim, Jong Hoon
Highlights: For cT1bN0M0 esophageal SCC, DCRT was commonly used as a second choice treatment. But DCRT showed equivalent survival to esophagectomy with less complications. DCRT should be recommended as one of standard treatments for all cT1bN0M0 ESCC. Abstract: Background and purpose: This study aimed to determine the equivalence between definitive chemoradiotherapy (DCRT) and radical esophagectomy in clinical T1bN0M0 esophageal squamous cell carcinoma (ESCC). Materials and methods: Among 282 patients with cT1bN0M0 ESCC, 238 underwent radical esophagectomy and 44 underwent DCRT. Both treatments were retrospectively compared overall survival (OS), progression-free survival (PFS), and complications. Results: The DCRT group exhibited poorer patient characteristics than the surgery group, especially with mean age (73 vs. 63 years), Eastern Cooperative Oncology Group (ECOG) status, and Charlson Comorbidity Index ( p  < 0.001, each). The median follow-up duration was 49.5 (range, 0.4–97.0) and 45.5 months (range, 5.0–112.0) in the surgery and DCRT groups, respectively. In the DCRT group, clinical complete response was achieved in 43 patients (97.7%) at 1 month after treatment. The 5-year OS rates were 75.8% and 68.8% ( p  = 0.135) and the 5-year PFS were 63.8% and 57.8% ( p  = 0.637) for the surgery and DCRT groups, respectively. Local recurrence rates were identical between the two groups (11.4% and 11.4%), but the distant metastasis rate was lower in the DCRT group ( n  = 1, 2.27% vs. n  = 29, 12.15%). Grade 3–4 hematologic toxicities were observed in 11 patients (25%) of the DCRT group, and 56 patients (23.5%) in the surgery group showed grade 3–5 surgical complications, including mortality ( n  = 5). Conclusion: Based on the non-inferior survival rates, recurrence patterns, and complication rates without critical surgical mortality, DCRT was comparable to esophagectomy for cT1bN0 esophageal squamous cell carcinoma.